Pre-Gaṅgeśa concept of Liṅgaparāmarśa: with special reference to Śaśadhara - Panda, Bhagaban (Bharatiya Kala Prakashan, 2009)
Study of Navyanyaya philosophy with refererence to Lingaparamarsa chapter in Nyayasiddhantadipa of Sasadhara, 10th cent. logician